Obstructive sleep apnea presenting as pseudopheochromocytoma - Marmouch, Hela (Pan Afr Med J, 2016)
A 52-year-old female with a history of poorly controlled resistant hypertension was admitted to our hospital with severe hypertension. She had a history of fatigue and intermittent episodes of palpitations. Laboratory evaluation was significant for elevated 24-h urinary catecholamine levels (3,5 times the upper normal levels). This case was presenting with a clinical and biochemical picture indistinguishable from that of pheochromocytoma. However, neither computed tomography nor meta-iodo-benzyl-guanidine scintigraphy detected any catecholamine-producing tumor in or outside the adrenal glands. Our patient was screened with full polysomnography because of heavy snoring, daytime somnolence and obesity. It revealed severe obstructive sleep apnea syndrome. After three months of continuous positive airway pressure therapy, the patient experienced resolution of his presenting symptoms, improved blood pressure control and normalization of his urinary catecholamine levels. This case highlights sleep disordered breathing as a potentially reversible cause of pseudo-pheochromocytoma.